Sonographic measurement of lower uterine segment thickness to predict uterine rupture during a trial of labor in women with previous Cesarean section: a meta‐analysis - Kok, N.; Wiersma, I. C.; Opmeer, B. C.; de Graaf, I. M.; Mol, B. W.; Pajkrt, E. (Ultrasound in obstetrics & gynecology, 2013)
ABSTRACT Objective To evaluate the accuracy of antenatal sonographic measurement of lower uterine segment (LUS) thickness in the prediction of risk of uterine rupture during a trial of labor (TOL) in women with a previous Cesarean section (CS). Methods PubMed and EMBASE were searched to identify articles published on the subject of sonographic LUS measurement and occurrence of a uterine defect after delivery. Four independent researchers performed identification of papers and data extraction. Selected studies were scored on methodological quality, and sensitivity and specificity of measurement of LUS thickness in the prediction of a uterine defect were calculated. We performed bivariate meta‐analysis to estimate summary receiver–operating characteristics (sROC) curves. Results We included 21 studies with a total of 2776 analyzed patients. The quality of included studies was good, although comparison was difficult because of heterogeneity. The estimated sROC curves showed that measurement of LUS thickness seems promising in the prediction of occurrence of uterine defects (dehiscence and rupture) in the uterine wall. The pooled sensitivity and specificity of myometrial LUS thickness for cut‐offs between 0.6 and 2.0 mm was 0.76 (95% CI, 0.60–0.87) and 0.92 (95% CI, 0.82–0.97); cut‐offs between 2.1 and 4.0 mm reached a sensitivity and specificity of 0.94 (95% CI, 0.81–0.98) and 0.64 (95% CI, 0.26–0.90). The pooled sensitivity and specificity of full LUS thickness for cut‐offs between 2.0 and 3.0 mm was 0.61 (95% CI, 0.42–0.77) and 0.91 (95% CI, 0.80–0.96); cut‐offs between 3.1 and 5.1 mm reached a sensitivity and specificity of 0.96 (95% CI, 0.89–0.98) and 0.63 (95% CI, 0.30–0.87). Conclusions This meta‐analysis provides support for the use of antenatal LUS measurements in the prediction of a uterine defect during TOL. Clinical applicability should be assessed in prospective observational studies using a standardized method of measurement. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.